2023
DOI: 10.1007/s12035-023-03315-w
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome-Mediated Neuronal-Microglial Crosstalk: a Therapeutic Substrate for the Familial C9orf72 Variant of Frontotemporal Dementia/Amyotrophic Lateral Sclerosis

Abstract: Intronic G 4 C 2 hexanucleotide repeat expansions (HRE) of C9orf72 are the most common cause of familial variants of frontotemporal dementia/amyotrophic lateral sclerosis (FTD/ALS). G 4 C 2 HREs in C9orf72 undergo non-canonical repeat-associated translation, producing dipeptide repeat (DPR) proteins, with various deleterious impacts on cellular homeostasis. While ve different DPRs are produced, poly(glycine-arginine) (GR) is amongst the most toxic and is the only DPR to accumulate in the associated clinically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Here, C9orf72 ALS/FTD iPSC-MG mono-cultures exhibit a comparable response to control iPSC-MG upon LPS stimulation. Further studies are necessary to determine if C9orf72 ALS/FTD iPSC-MG present or exacerbate an inflammatory phenotype when stimulated to induce more specific inflammatory responses, such as activation of the inflammasome via the NLRP pathway (Fu et al, 2022 ; Trageser et al, 2023 ) or co-stimulation of LPS and IFNγ to specifically activate pro-inflammatory pathways (Kann et al, 2022 ). Furthermore, it will be interesting to examine inflammatory responses when iPSC-MG are co-cultured with diseased neurons or astrocytes knowing that direct contact of iPSC-MG with CNS cells can influence their gene expression (Abud et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, C9orf72 ALS/FTD iPSC-MG mono-cultures exhibit a comparable response to control iPSC-MG upon LPS stimulation. Further studies are necessary to determine if C9orf72 ALS/FTD iPSC-MG present or exacerbate an inflammatory phenotype when stimulated to induce more specific inflammatory responses, such as activation of the inflammasome via the NLRP pathway (Fu et al, 2022 ; Trageser et al, 2023 ) or co-stimulation of LPS and IFNγ to specifically activate pro-inflammatory pathways (Kann et al, 2022 ). Furthermore, it will be interesting to examine inflammatory responses when iPSC-MG are co-cultured with diseased neurons or astrocytes knowing that direct contact of iPSC-MG with CNS cells can influence their gene expression (Abud et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, both treatments caused reduced lysosomal localization of the C9orf72 complex (C9orf72, SMCR8, and WDR41), which localizes to lysosomes and the cytoplasm [90][91]. Mutations in this complex lead to familial amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) [92], and recent studies demonstrated that genetic ablation of the C9orf72 complex caused sustained NLRP3 inflammasome activation in microglia [93][94]. Previous lysosomal proteomics of damaged lysosomes, induced by either LLoMe or GPN [95][96], only identified one protein of this complex [88][97].…”
Section: Resultsmentioning
confidence: 99%
“…Microglia are the most important immune cells in the brain and play an important role in maintaining the health of neurons and homeostasis of niches [44]. Activation of the NLRP3 inflammasome in microglia is known to be an important pathological factor in ALS [45]. Priming and activation are two essential steps for activating the canonical NLRP3 inflammasome [46].…”
Section: Discussionmentioning
confidence: 99%